ANALISIS PENGUASAAN KATA KERJA â€œGAIBIANâ€DAN â€œZHUANBIANâ€ PADA MAHASISWA ANGKATAN 2016 PENDIDIKAN BAHASA MANDARIN - Purwati, Purwati; Ina, Ina; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractVerbs is a words that express the state of action behavior, physiology or psychology. There are many verbs in Chinese, which is â€œgaibianâ€ and â€œzhuanbianâ€. Although the meanings of these two words are similar, their usages are different. Therefore, Chinese students tend to misuse these two words. In order to understand the mastery of verb â€œgaibianâ€ and â€œzhuanbianâ€ by 2016 Chinese majors of Tanjungpura University, the author use the method to test the student and analyses the difficulties of â€œgaibianâ€ and â€œzhuanbianâ€. The test results show that studentsâ€™mastery of â€œgaibianâ€ is better than â€œzhuanbianâ€. The correct rate of â€œgaibianâ€ is 70%, the corrate rate of â€œzhuanbianâ€ is only 61%. When analyzing the difficulties, the author finds that the good usage that students graspÂ is â€œgaibianâ€ can bring â€œleâ€ and â€œguoâ€. Nominal objects and indicators of â€œzhuanbianâ€ change from one situation to another. Unmastered usage is â€œgaibianâ€ show a change caused by external forces, and â€œzhuanbianâ€ show its own change generally to be better and higher level.Â Keywords: Verbs Word, Gaibian and zhuanbian, Condition of Mastery